2002
DOI: 10.1159/000056155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 17β-Estradiol on Intracellular Ca<sup>2+</sup> Levels in Renal Tubular Cells

Abstract: The effect of 17β-estradiol on intracellular Ca2+ concentrations ([Ca2+]i) in Madin Darby canine kidney cells was investigated by using the fluorescent dye fura-2. 17β-Estradiol (5–100 µmol/l) induced instantaneous increases in [Ca2+]i in a concentration-dependent manner. Ca2+ removal inhibited 45 ± 15% of the Ca2+ signal. In Ca2+-free medium, pretreatment with 50 µmol/l 17β-estradiol abolished the [Ca2+]i Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…E2 was previously found to regulate mESC proliferation via both genomic and non‐genomic pathways (Han et al, 2006). E2 has been reported to trigger Ca 2+ release or Ca 2+ influx via non‐genomic pathway in various cell types (Picotto et al, 1999; Perret et al, 2001; Chen et al, 2002). In the present investigation, we found that E2 could not elicit any Ca 2+ influx within 10 min in mESCs (E2 at concentrations from 1 pM to 1 µM were tested; data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…E2 was previously found to regulate mESC proliferation via both genomic and non‐genomic pathways (Han et al, 2006). E2 has been reported to trigger Ca 2+ release or Ca 2+ influx via non‐genomic pathway in various cell types (Picotto et al, 1999; Perret et al, 2001; Chen et al, 2002). In the present investigation, we found that E2 could not elicit any Ca 2+ influx within 10 min in mESCs (E2 at concentrations from 1 pM to 1 µM were tested; data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The inositol‐1,4,5‐trisphosphate‐sensitive Ca 2+ store is the major Ca 2+ store that releases Ca 2+ into the cytosol when cells are stimulated by endogenous agents, such as bradykinin and ATP [12,13]. But exogenous agents can release Ca 2+ from inositol‐1,4,5‐trisphosphate‐insensitive stores [15].…”
mentioning
confidence: 99%
“…But exogenous Author for correspondence: Chung-Ren Jan, Department of Medical Education and Research, Kaohsiung Veterans General Hospital, Kaohsiung 813, Taiwan (fax +886-7-3468056, e-mail crjan@isca.vghks.gov.tw). agents can release Ca 2+ from inositol-1,4,5-trisphosphateinsensitive stores [15].…”
mentioning
confidence: 99%
“…The Madin Darby canine kidney (MDCK) cell line is a useful model for renal cell research. It has been shown that in this cell , [Ca 2+ ] i can be increased in response to the stimulation of various endogenous and exogenous compounds, such as ATP (Jan et al 1998a), linoleamide (Huang & Jan 2001), and oestrogens (Chen et al 2002) etc.…”
mentioning
confidence: 99%